Evaluasi Sistem Informasi Akademik (SIAK) Menggunakan Evaluasi Heuristik Dan Kuesioner Pengalaman Pengguna - Ariawan, Wayan Eka; Gunawan, I Made Agus Oka; Putra, I Made Agus Widiana (Universitas Tabanan, 2024)
This study evaluates the interface and user experience of the Academic Information System (SIAK) at Tabanan University, developed by PT. Hoki Group. SIAK is used to manage academic information such as student registration, class scheduling, and grade recording. The evaluation aims to identify user issues and analyze their responses while using the system. Heuristic evaluation methods and the User Experience Questionnaire (UEQ) were used to assess the interface and user experience. The results showed average ratings of good in attractiveness, clarity, efficiency, and novelty, and very good in stimulation. However, nine main issues were found, including improper placement of the search feature, lack of error notifications, and incomplete menus. Interface improvement recommendations focus on addressing these issues to enhance the quality of SIAK. The findings of this study are expected to help developers improve the user interface (UI) elements and enhance the overall user experience.